2011
DOI: 10.1103/physrevb.84.045104
|View full text |Cite
|
Sign up to set email alerts
|

Valence transition in (Pr,Ca)CoO3cobaltites: Charge migration at the metal-insulator transition

Abstract: X-ray absorption spectroscopy measurements in Pr 0.5 Ca 0.5 CoO 3 and (Pr,Y) 0.55 Ca 0.45 CoO 3 compositions reveal that the valence of praseodymium ions is stable and essentially +3 (Pr [4f 2 ]) in the metallic state, but abruptly changes when carriers localize approaching the oxidation state +4 (Pr [4f 1 ]). This mechanism appears to be the driving force of the metal-insulator transition. The ground insulating state of Pr 0.5 Ca 0.5 CoO 3 is an homogeneous Co 3.5-δ state stabilized by a charge transfer from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 34 publications
(77 reference statements)
5
50
1
Order By: Relevance
“…For the prototypical compound Pr 0.5 Ca 0.5 CoO 3 this valence shift was confirmed and determined quantitatively with the identification of the Pr 4þ -related Schottky peak in heat capacity measurements 12 and by X-ray absorption spectroscopy at the Pr L 3 edge. 13 Similar evidence was presented also for the Pr 0.7 Ca 0.3 CoO 3 systems doped by Y, [14][15][16] Sm, 17 and Tb. 18 Many studies have been done especially on the (Pr 1Ày Y y ) 0.7 Ca 0.3 CoO 3 system, which displays a MI-SS transition and partial Pr 3þ !…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…For the prototypical compound Pr 0.5 Ca 0.5 CoO 3 this valence shift was confirmed and determined quantitatively with the identification of the Pr 4þ -related Schottky peak in heat capacity measurements 12 and by X-ray absorption spectroscopy at the Pr L 3 edge. 13 Similar evidence was presented also for the Pr 0.7 Ca 0.3 CoO 3 systems doped by Y, [14][15][16] Sm, 17 and Tb. 18 Many studies have been done especially on the (Pr 1Ày Y y ) 0.7 Ca 0.3 CoO 3 system, which displays a MI-SS transition and partial Pr 3þ !…”
Section: Introductionsupporting
confidence: 59%
“…This process is compensated by the valence change of some Pr 3þ ions to Pr 4þ ions; 13,15 we determined the final amount to be 0.11 Pr 4þ per f. u. based on the Schottky peak in heat capacity under ZFC (experiment to be published elsewhere). Surprisingly, we detected a certain reduced amount of Pr 4þ even after a cooling run in a 9-T field, when the MI-SS transition was suppressed and the y ¼ 0.0625 sample remained in the metallic state.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, useful material properties such as temperature-induced metal-insulator transitions and thermoelectricity have been reported as well [4][5][6][7][8][9]. In the work presented here we study microwave (MW) -assisted synthesis of the RE cobaltites (RE)CoO3 (RE = La -Dy) series in order to demonstrate the feasibility of the MW technique for this class of materials.…”
Section: Introductionmentioning
confidence: 99%
“…11,13,15 Over a temperature interval as large as HT-LT=40 K, however, one can consider that the greatest part of the valence change is completed. 11,13,15 Therefore, we adopt hereafter the approximation that [Pr 4+ ] goes from 0.13 (at LT) to 0 (at HT), allowing the analysis to be focused on the variation of [Co 3+ HS] across the transition.…”
Section: Position Of the Problemmentioning
confidence: 99%
“…[1][2][3] Starting from 2010 however, it was shown that the stabilization of a mixed Pr 3+ /Pr 4+ valence at low temperatures was also involved in this transition. 8,[9][10][11][12][13] In addition to the SST transition affecting the Co 3+ , a Pr 4+ -to-Pr 3+ transformation takes place when crossing T* upon warming, being counterbalanced by a corresponding change from Co 3+ to Co 4+ . 8,[10][11][12] The transition at T* in these compounds can thus be regarded as a coupled valence and spinstate transition (VSST).…”
Section: Introductionmentioning
confidence: 99%